Absence of cholinergic spectra in the placenta of pregnancies affected by severe growth restriction using proton magnetic resonance spectroscopy. (18th April 2012) - Denison, FC; Walker, J; Marshall, I; Norman, JE; Semple, S
Abstract : Background: Uteroplacental insufficiency is the main cause of fetal growth restriction (FGR) and stillbirth. Current diagnostic tests for uteroplacental insufficiency are limited. Recent advances in proton (1H) magnetic resonance spectroscopy (MRS) and magnetic resonance imaging (MRI) enable real-time investigations of physiological and pathological processes. We hypothesised that MRS may offer a novel non-invasive method of assessing placental function in vivo . Objective: To establish the feasibility of undertaking 1H MRS in the placenta in vivo using 3T MRI and to undertake the first proof-of concept study of placental 1H MRS in women with healthy pregnancies compared to those complicated by suspected uteroplacental insufficiency and FGR. Study design: Following method development in healthy pregnant volunteers (n=3), in vivo placental 1H MRS was performed using in 3 pregnancies with FGR and 3 healthy controls. Oxygenation and acid-base balance were determined at birth where possible. Results: The feasibility of undertaking placental 1H MRS was established during the method development scans. In healthy pregnancies, choline and lipid spectral peaks were clearly detected in all placenta using 1H MRS. In contrast, in pregnancies complicated by FGR, despite preservation of the lipid peak and normal cord gases, the choline peak was absent from all placentae (Figure 1 ). Conclusion: In this first proof-of-concept study, we established the feasibility of undertaking placental 1H MRS in healthy pregnancies and those complicated by FGR. Absence of a choline peak in placenta from pregnancies complicated by FGR may represent a novel non-invasive diagnostic marker of severe uteroplacental insufficiency indicative of critical placental failure.